Study of calcium-magnesium-aluminum-silicate (CMAS) glass and glass-ceramic sealant for solid oxide fuel cells - Reddy, Allu Amarnath
A parent glass within the CaO-MgO-Al2O3-SiO2 system and resulting glass ceramics (GCs) have been appraised for solid oxide fuel cells (SOFCs) sealing applications. The sintering behavior was investigated by differential thermal analysis and hot stage microscopy. The glass composition exhibited single-stage shrinkage behavior with high sintering ability, and a suitable viscosity of 10(7.1) dPa s at the SOFCs operating temperature 900 degrees C. X ray diffraction in conjunction with the Rietveld-RIR technique were employed to quantify the crystalline and amorphous phases in the GCs sintered at 900 degrees C for 1 h and 850 degrees C for 300 h. The coefficients of thermal expansion (CTE) measured were 9.7 x 10(-6) K-1 (200-500 degrees C) and similar to 10.1 x 10(-6) K-1 (200-700 degrees C) for glass and GCs, respectively, in good agreement with those typical for SOFC components. Weibull analysis was applied on the three-point bend data of GCs in order to obtain the mechanical strength distribution, characteristic strength and Weibull modulus. Well matching CTE, flexural strength values, good sintering behavior and adhesion to the other components in air atmosphere allow proposing this glass composition as promising candidate for further experimentation as sealant for SOFCs. (C) 2012 Elsevier B.V. All rights reserved.